Assistência às pessoas portadoras de deficiência física: acessibilidade aos serviços especializados no município de Fortaleza - Brasil, Ana Cristhiha de Oliveira (2002)
In 1991 lhe population of Ceará was composed of 1.18% of people having disability (PCB). Such people, because of being different, face a lot of difficulties performlng their daily activities, as well as having access to the their sdlf sustenance, health, education, leisure, and to the urban spaces of the city in which they live. In this research, we initiálly made a literature review in order to outline a broad survey about the problems concerning PDB, as well as to describe the public policies related to health care for these people. In a second moment, we made a cross- sectional study from July to October 2001, aiming at describing the itínerary covered by physically disabled people (PDP) immediately after the injury gone through or after the manifestatlon of the pathology, until the access to the specialized health Service investigated. This was done by applylng a questionnaire to the PDP who seceived treatment at the institution chosen for the study and which belongs to the Sistema Único de Saúde (SUS) which provides specialized Services to health recovery in Fortaleza. When making a descriptive statístical analysis of the data, the results showed that: (I) The ones who had most access to the Service were those having Hemiplegia (70.6°%); (ii) Among the PDP, 75.4°% stated that, on average, it took them around 280 days after the problem occurred to access this type of Service, although 93.4% were referred to it; (iii) The PDP (77%) did not mention any kind ofdifficulty to obtain a vacancy, as they took advantage of a circle of friends around them and/or around the institution to get it. Among the obstacles to the access to the daily treatment are the cost and the way of travei which were overcome by the PDP due to great need of the treatment, to the existing cooperation among them and to circle of friends. The lack of knowledge about specialized Services near home shows the non-existence of a reference and contrareference System slnce many of the people had access to this type of Service still in hospital. So, it is extremely important that the Sistema Único de Saúde pays more attention to the planning of health care to this population group, as well as to the implementation of the State Health Care Net of the PDB Fortaleza city so as to increase, without or wíth inability, the Hfe expectancy of these custorners.